Interference‐Limited Dynamic Resource Management for an Integrated Satellite/Terrestrial System. Issue 4 (1st August 2014) - Park, Unhee; Kim, Hee Wook; Oh, Dae Sub; Ku, Bon‐Jun
Abstract : An integrated multi‐beam satellite and multi‐cell terrestrial system is an attractive means for highly efficient communication due to the fact that the two components (satellite and terrestrial) make the most of each other's resources. In this paper, a terrestrial component reuses a satellite's resources under the control of the satellite's network management system. This allows the resource allocation for the satellite and terrestrial components to be coordinated to optimize spectral efficiency and increase overall system capacity. In such a system, the satellite resources reused in the terrestrial component may bring about severe interference, which is one of the main factors affecting system capacity. Under this consideration, the objective of this paper is to achieve an optimized resource allocation in both components in such a way as to minimize any resulting inter‐component interference. The objective of the proposed scheme is to mitigate this inter‐component interference by optimizing the total transmission power — the result of which can lead to an increase in capacity. The simulation results in this paper illustrate that the proposed scheme affords a more energy‐efficient system to be implemented, compared to a conventional power management scheme, by allocating the bandwidth uniformly regardless of the amount of interference or traffic demand.